To simplify the expression, let's first convert the mixed numbers to improper fractions:
The mixed number -2 1/4 can be written as -9/4.
The mixed number -5 2/3 can be written as -17/3.
Now let's multiply the fractions:
-2 1/4 * -5 2/3 = (-9/4) * (-17/3)
Next, multiply the numerators and denominators:
-9 * -17 = 153 (numerator)
4 * 3 = 12 (denominator)
So, -2 1/4 * -5 2/3 = 153/12.
Finally, simplify the fraction:
153/12 can be simplified to 51/4.
Therefore, -2 1/4 * -5 2/3 equals 51/4.
−2 1/4×(−5 2/3
3 answers
thats wrong
Apologies for the mistake. Let's correct it.
To simplify -2 1/4 * -5 2/3, let's first convert the mixed numbers to improper fractions:
-2 1/4 = -9/4
-5 2/3 = -17/3
Now let's multiply the fractions:
-9/4 * -17/3
When multiplying fractions, multiply the numerators together, and the denominators together:
(-9 * -17) / (4 * 3) = 153/12
Now, let's simplify the fraction:
The numerator and denominator share a common factor of 3:
153/12 = (3 * 51) / (3 * 4)
Simplifying further:
(3/3) * (51/4) = 51/4
So, -2 1/4 * -5 2/3 simplifies to 51/4.
To simplify -2 1/4 * -5 2/3, let's first convert the mixed numbers to improper fractions:
-2 1/4 = -9/4
-5 2/3 = -17/3
Now let's multiply the fractions:
-9/4 * -17/3
When multiplying fractions, multiply the numerators together, and the denominators together:
(-9 * -17) / (4 * 3) = 153/12
Now, let's simplify the fraction:
The numerator and denominator share a common factor of 3:
153/12 = (3 * 51) / (3 * 4)
Simplifying further:
(3/3) * (51/4) = 51/4
So, -2 1/4 * -5 2/3 simplifies to 51/4.